Origin and oscillation of neutrinos in the matter - Valenzuela, Mississippi (2025)
The phenomenon of neutrino oscilation is a purely quantum effect  and can roughly be interpreted as a change in flavor of the neutrinos. For the oscillation phenomenon to take place, it is necessary that the neutrinos have a mass different to zero. Therefore, the experimental discovery of neutrino oscillation is the first incontrovertible evidence of physics that is not included in the theoretical framework of the standard model. According to the standard model (SM) of particle physics, neutrinos are massless particles. The neutrino is very difficult to detect because it interacts weakly with ordinary matter, that is, this particle only couples to weak gauge bosons. For this reason, until today it has not been possible to carry out its complete characterization . However, this elusive particle is one of the most abundant elementary particles in the Universe and is expected to play a fundamental role in giving a "picture" of the early Universe. Currently, there is a large number of neutrinos remaining from the Big Bang, that is, generated in the big explosion and still traelling in space. Neutrino physics is one of the research topics in models beyond the standard model, which are currently being studied in searches for new physics. Therefore, in this work it is considered that neutrinos are massive particles, which acquire their mass through the I, II and III seesaw mechamism.